METEOROLOGICAL OBSERVATIONS ALONG A TRAVERSE ROUTE FROM COAST TO DOME FUJI STATION, ANTARCTICA, RECORDED BY AUTOMATIC WEATHER STATIONS IN 1995 - カメダ, タカオ; タカハシ, シュウヘイ; エノモト, ヒロユキ; アズマ, ノブヒコ; シライワ, タカユキ; コダマ, ユウジ; フルカワ, テルオ; ワタナベ, オキツグ; /; KAMEDA, Takao; TAKAHASHI, Shuhei; ENOMOTO, Hiroyuki; et al. (National Institute of Polar Research, 1997)
P(論文) This paper focuses on instrumentation and observational results of eight Automatic Weather Station (AWS) units in East Queen Maud Land, Antarctica 1995. The AWS units were installed at six sites on the ice sheet from coast to inland : the site nearest to the coast (H21) was located at 60km at 1076m altitude and a site farthest from the coast (Dome Fuji Station) was located about 920km inland at 3810m altitude. Two types of AWS units (CMOS and ARGOS) were employed. Air temperatures at H21 and Dome Fuji Station change from +2.3 to -44.4℃ and -23.3 to -80.1℃, respectively. Monthly mean July temperatures in eight AWS data are systematically higher than June and August temperatures, respectively. During the period of temperature increase in July, atmospheric pressure also increased. Wind speed during the whole period could only be obtained at MD180 at which glazed surface was observed. Prevailing wind (south-east : SE) at Relay Point covers 40% of the total wind direction, and wind from the east north-east slightly prevails (11%) at Dome Fuji Station. Atmospheric pressure at Relay Point drops in May and September, and increases in July and December. Monthly mean lapse rates on snow surface were calculated using AWS data. Annaul mean lapse rates obtained by the AWS data were systematically lower than that obtained by 10m snow temperatures in Mizuho Plateau. Increase of temperature difference between air and snow surface with altitude will be a reason for the phenomenon. departmental bulletin paper